All-atom molecular dynamics study of impact fracture of glassy polymers. I: Molecular mechanism of brittleness of PMMA and ductility of PC. (12th September 2019) - Fujimoto, Kazushi; Tang, Zhiye; Shinoda, Wataru; Okazaki, Susumu
Abstract: Molecular mechanism of brittle and ductile impact fractures of glassy polymers has been investigated. We performed atomistic molecular dynamics (MD) calculations for two glassy polymers, brittle poly(methyl methacrylate) (PMMA) and ductile polycarbonate (PC) using the dissociative force fields. The systems were prepared as realistic as possible such that they reproduced the experimental molecular weight distribution, tacticity, radius of gyration, and entanglement density. The calculated system simulated a small portion of the macroscopic specimen near the notch. The simulations adopted a uniaxial extension condition with the lateral pressure maintained as 1 atm. Under this condition, our atomistic models reproduced the brittle fracture of PMMA via cavitation and ductile fracture of PC via shear yielding and strain hardening. The fracture pathways were determined only by the differences in the material. A conceptual bridge between microscopic simulations and macroscopic experimental observations was provided. The brittle fracture of PMMA is found to be caused by the less flexible backbones with fewer entanglements as well as the inhomogeneity of the material. This contrasts with the finding that more flexible backbones with denser entanglement network result in ductility for PC. Graphical abstract: Image 1